Impatience among preschool children and their mothers - Fabian Kosse; Friedhelm Pfeiffer (Institute for the Study of Labor (IZA), 2011)
Using experimental data of children and their mothers, this paper explores the intergenerational relationship of impatience. The child's impatience stems from a delay of gratification experiment. Mother's impatience has been assessed by a choice task where the mothers faced trade-offs between a smaller-sooner and a larger-later monetary reward with a delay of six or twelve months. The findings demonstrate an intergenerational relationship in short-run decision making. Controlling for mother's and child's characteristics the child's impatience at preschool age is significantly correlated with the six month maternal reservation interest rate.
urn:nbn:de:101:1-201203014833
Keywords: C93; D03; D90; 330; time preferences; impatience; intergenerational transmission; field experiments; Kinder; Mütter; Zeitpräferenz; Generationenbeziehungen; Feldforschung